2014
DOI: 10.1038/ncomms6094
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate-hosted methanotrophy represents an unrecognized methane sink in the deep sea

Abstract: The atmospheric flux of methane from the oceans is largely mitigated through microbially mediated sulphate-coupled methane oxidation, resulting in the precipitation of authigenic carbonates. Deep-sea carbonates are common around active and palaeo-methane seepage, and have primarily been viewed as passive recorders of methane oxidation; their role as active and unique microbial habitats capable of continued methane consumption has not been examined. Here we show that seep-associated carbonates harbour active mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 68 publications
(148 reference statements)
5
69
0
Order By: Relevance
“…The persistence of ANME Archaea and microbial aggregates typically associated with AOM in low-activity samples suggests that even at fluxes that do not support established sulfide-based chemosynthetic communities at the seabed (microbial mats or chemosynthetic clam beds), potential for anaerobic methanotrophy remains (Marlow et al, 2014). These findings imply that methanotrophic potential is pervasive on and below the seafloor across substrate types, and the degree to which ancient seep deposits preserve signals of microbial community succession is unknown.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…The persistence of ANME Archaea and microbial aggregates typically associated with AOM in low-activity samples suggests that even at fluxes that do not support established sulfide-based chemosynthetic communities at the seabed (microbial mats or chemosynthetic clam beds), potential for anaerobic methanotrophy remains (Marlow et al, 2014). These findings imply that methanotrophic potential is pervasive on and below the seafloor across substrate types, and the degree to which ancient seep deposits preserve signals of microbial community succession is unknown.…”
Section: Discussionmentioning
confidence: 80%
“…Aerobic methanotrophic activity has been documented using radiotracer methods in sediments and carbonates from both actively seeping and low-activity locations at Hydrate Ridge (Marlow et al, 2014). Surprisingly, the majority of samples lacked 16S rRNA evidence of known aerobic methanotrophs with the exception of AC-5120, a dolomite sample collected from an active seep site, where sequences affiliated with gammaproteobacterial Methylococcales comprised 8% of recovered sequences (Supplementary Data file 2a).…”
Section: Bacterial Community Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…This led to the belief that ammonium and methane were inert under anoxic conditions. However, recent studies using molecular techniques have shown that anaerobic methane oxidation can be carried out by a syntrophic consortium made up of an archaeon and a sulfate-reducing bacterium, although it has been suggested that some archaea can oxidize CH 4 without the need for a syntrophic bacterial partner (Boetius et al 2000;Marlow et al 2014). …”
Section: The Energetic Basis Of Lifementioning
confidence: 99%